Policies for the Agricultural Knowledge and Innovation System in southern Italian areas: the state of the art - Vagnozzi, Anna; Giarè, Francesca (Italian Review of Agricultural Economics, 2025)
This paper analyses the state of innovation in Italian agriculture, with a particular focus on southern areas, and examines the evolution of European Agricultural Knowledge and Innovation System (AKIS) policies over the last 15 years. Using data from the Italian National Institute of Statistics (ISTAT) Agricultural Census and Farm Accountancy Data Network (FADN)-derived indicators, this study highlights a markedly low propensity for innovation among farms in southern Italy, linked to structural weaknesses; limited digitalisation; and suboptimal performance across economic, environmental, and social dimensions. Despite these challenges, regional policy strategies appear largely uniform throughout Italy, showing little adaptation to the specific needs of lagging areas. The review of rural development interventions illustrates persistent difficulties in implementing advisory services, contrasted with stronger uptake and better financial performance of innovation-oriented measures, particularly Operational Groups under the European Innovation Partnership for Agricultural Productivity and Sustainability. The Italian Common Agricultural Policy Strategic Plan for 2023-2027 introduces mechanisms to strengthen system coordination and enhance advisory and knowledge-exchange functions; however, budget allocations remain modest, especially in southern Italy. In conclusion, fragmentation within the Italian AKIS, coupled with cautious regional programming, risks perpetuating existing disparities and limiting the agricultural sector’s capacity to address structural, environmental, and competitiveness challenges.